2010
DOI: 10.1080/13648470903572366
|View full text |Cite
|
Sign up to set email alerts
|

The potential of the internet for alternative caring practices for health

Abstract: The practices of health care in late modernity are informed by competing visions of the ideal human and the nature of care. Western societies typically characterise the ideal human as independent and self-reliant. The resultant welfare systems provide temporary havens away from the everyday, competitive spaces of capitalist societies, termed here the enclave model. Social scientists problematise this model on several grounds: the construction of pathologised and medicalised body forms; the neglect of caring pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Atkinson and Ayers (2010) argue that the proliferation of web based health care sites offer an alternate model of care, one rooted in a model of caring relationships that traverse geographic distance (See also Broom 2005). Scholars have even used cyber studies-in the form of Facebook messages-to predict postpartum depression in new mothers in the US (De Choudhury et al 2014).…”
Section: The Internet and The Altered Landscape Of Family Lifementioning
confidence: 97%
“…Atkinson and Ayers (2010) argue that the proliferation of web based health care sites offer an alternate model of care, one rooted in a model of caring relationships that traverse geographic distance (See also Broom 2005). Scholars have even used cyber studies-in the form of Facebook messages-to predict postpartum depression in new mothers in the US (De Choudhury et al 2014).…”
Section: The Internet and The Altered Landscape Of Family Lifementioning
confidence: 97%
“…(Emphasis added) When Montse says that the Internet saved her life, she is not talking about relief for her medical condition; she is talking about feeling alive, being 'in the world' and connected to others who support her and help her to manage the effects of the illness on her life, including the possibility of social death, as implied in her reference to a bed-bound life without social interaction. The Internet offers virtual social life and interaction that provides new forms of moral, emotional, and social support (Nettleton et al, 2002), and alternative caring practices-both caring for and caring about (Atkinson and Ayers, 2010;Burrows et al, 2000)-that 'save' not the body but the souls of those who are homebound and chronically ill.…”
Section: Illness the Internet And Social Lifementioning
confidence: 99%
“…3 Participation in patients' online communities, forums, self-help groups, blogs, and other health-related web pages is becoming an important source of moral, emotional, and social support 4 because it enables the sharing of common experiences and interests (Burrows et al, 2000;Josefsson, 2005;Nettleton et al, 2002). Moreover, the Internet has created conditions for the emergence of new forms of care (Atkinson and Ayers, 2010;Burrows et al, 2000)-both caring for and caring about-not only among the chronically ill but also between sick and healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that Internet can not only enhance clinical and material care which enables managing diseases more effectively but also can act as spaces where people can care for themselves and others (Atkinson and Ayers 2010). The context of ICT interventions in healthcare such as telemedicine, Web 2.0, HIS systems, electronic medical records, m-health and so on provides fertile areas to investigate the changing logics of the institution of healthcare.…”
Section: Directions For Future Researchmentioning
confidence: 99%